PERBEDAAN TINGKAT PENGETAHUAN IBU HAMIL PRIMIGRAVIDA YANG MELAKUKAN KUNJUNGAN ANTENATAL PADA DOKTER SPESIALIS OBGYN DENGAN BIDAN DI KOTA PADANG - Susanti Apriani; Syahredi Syaiful Adnani; Hafni Bachtiar (Universitas Andalas, 2019)
The maternal mortality rate in Indonesia Demographic and Health Survey (IDHS) 2012, increased sig- nificantly to 359 per 100,000 births hidup.1 Obtained in Household Health Survey (Survey) 2001 mater- nal mortality rate can be lowered only by basic health services such as antenatal. Based on a UNICEF report, only about 45% were informed about the signs of pregnancy complications. This research was conducted to determine the cross sectional differences in the level of knowledge of pregnant women who had antenatal care at obstetricians and midwives in the city of Padang. Primigravida pregnant women who visit antenatal care at obstetricians and midwives in Padang City, amounting to 73.8% have a high level of knowledge. There were no differences in the level of knowledge of pregnant women who had antenatal care at obstetrician (p> 0.05)Keywords: Antenatal, Midwives, Obstetrician, knowledge